Mexico : Experiences with Pro-Poor Expenditure Policies - Corbacho, Ana.; Schwartz, Gerd. (Washington, D.C. : International Monetary Fund, 2002)
Against the background of Mexico's persistently high degree of inequality, this paper analyzes the country's experience with pro-poor policies over the last decade. A number of important government initiatives, implemented since the mid-1990s, have aimed at improving distributional equity through pro-poor expenditure programs, while at the same time seeking to increase the efficiency of public spending. This paper reviews these initiatives and outlines some additional policy options.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet